Informed shared decision making: An exploratory study in pharmacy. - Kassam R; Volume-Smith C; Albon SP (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Introduction: A study was undertaken to examine the feasibility of using the physician-based Informed Shared Decision Making (ISDM) framework for teaching pharmacy students competencies to effectively develop therapeutic relationships with patients. Objectives: To: (1) assess the relevance and importance of the physician-developed ISDM competencies for pharmacy practice, (2) determine which competencies would be easiest and hardest to practice, (3) identify barriers to implementing ISDM in pharmacy practice, and (4) identify typical situations in which ISDM is or could be practiced. Methods: Twenty pharmacists representing 4 different practices were interviewed using a standardized interview protocol. Results: Pharmacists acknowledged that majority of the physician-based competencies were relevant to pharmacy practice; although not all competencies were considered to be most important. Competency #1 (Develop a partnership with the patient) was found to be the most relevant, the most important and the easiest to practice of all the competencies. While no one competency was identified as being hard to practice, there were several barriers identified to practicing ISDM. Finally, pharmacists expressed that patients with chronic conditions would be the most ideal for engaging in ISDM.Conclusion: While pharmacists believed that the ISDM model could provide a framework for pharmacists to develop therapeutic relationships with their patients, the group also identified obstacles to engaging successfully in this relationship.